Amorphous metal oxide thin film transistors for printable electronics - Chen, Yuxin (2015)
Printed electronics desire to lower the cost of electronics manufacturing by using cheaper and inexpensive production techniques that conventional silicon manufacturing cannot imitate. Applications for low-cost printed electronics consist of radio frequency identification (RFID) tags, electronic sensors, displays, data storage, packaging, and printed circuit boards (PCB). Transistors make up the basic foundation of such circuits and devices. In this project, Indium Zinc Tin Oxide layers (IZTO) with various chemical compositions1 are used as the semiconductor layer of thin film transistors, forming the active channel layer. This helps us to find out the best possible composition with respect to transistor performance parameters like mobility, sub threshold swing and on – off ratio. Subsequently, altering the annealing temperature and annealing atmosphere without significant electrical characteristics degradation and film quality is the foremost target of this work2. Having a lower annealing temperature makes the manufacturing process suitable to be applied to transparent and flexible substrates like glass, Polyethylene 2, 6-naphthalate (PEN) and Polyethylene terephthalate (PET). Dependence of mobility, threshold voltage and current on-off ratio with different parameters are thoroughly studied. Indium Zinc Tin Oxide (IZTO) thin film transistors (TFTs) with mobility of 4.344cm2V-1s-1, current on-off ratio of 1E+5 and threshold voltage of -25.0V was obtained with a processing temperature of 400oC when working with a solution processed technique3.